1986
DOI: 10.1007/bf01260912
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of the Ca2+-antagonist nimodipine on dopamine metabolism in mouse brain

Abstract: The effects of the Ca2+-antagonist nimodipine on central dopamine (DA) neurons in mice were investigated in vivo. Nimodipine caused a dose-dependent decrease in the DA metabolite 3-methoxytyramine (3-MT) in striatum and the limbic region. If the brains were microwave radiated immediately after decapitation in order to minimize post-mortal accumulation of 3-MT, the effect of nimodipine was less pronounced and statistically not significant. Nimodipine markedly decreased the accumulation of 3-MT induced by pargyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 28 publications
1
8
1
Order By: Relevance
“…Results with the dihydropyridine calcium channel blockers are less clearcut; Middlemiss (1985), Middlemiss & Spedding (1985) and Bourson et al (1989) found no effect on either release or metabolite levels, whereas others have demonstrated inhibition of neurotransmitter release (Nordstrbm et al, 1986;Pileblad & Carlsson, 1986) or even, in the case of dopamine, an increase (Nordstrom et al, 1986). The effects of Bay K 8644, referred to above, can be reversed by the dihydropyridine calcium channel blockers suggesting that when activated, L-type calcium channels can affect neurotransmitter release, but that normally they play a negligible role.…”
Section: Discussionmentioning
confidence: 99%
“…Results with the dihydropyridine calcium channel blockers are less clearcut; Middlemiss (1985), Middlemiss & Spedding (1985) and Bourson et al (1989) found no effect on either release or metabolite levels, whereas others have demonstrated inhibition of neurotransmitter release (Nordstrbm et al, 1986;Pileblad & Carlsson, 1986) or even, in the case of dopamine, an increase (Nordstrom et al, 1986). The effects of Bay K 8644, referred to above, can be reversed by the dihydropyridine calcium channel blockers suggesting that when activated, L-type calcium channels can affect neurotransmitter release, but that normally they play a negligible role.…”
Section: Discussionmentioning
confidence: 99%
“…The dosing regimen was chosen according to the literature (13,17,18). The clinical score was significantly attenuated in nimodipinetreated mice in both the typical and atypical EAE groups ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Proapoptotic effects of DMSO or ethanol alone were also excluded by performing corresponding vehicle-control experiments. To ensure that our in vitro dose of nimodipine was clinically relevant, we studied the literature closely and tested doses that already had been used in several CNS disease models (13,18,50,51). The dose used for cell culture had been shown to induce equivalent effects in patients (e.g., reduced stress-mediated effects after brain surgery and decreased excitotoxicity) (51).…”
Section: Methodsmentioning
confidence: 99%
“…This is in conflict with our result. Nimodipine was reported to reduce the synthesis as well as the release of dopamine in mouse brain (31,32). The reduction of dopamine synthesis by nimodi pine may affect the ambulatory increment by ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the ambulation-increasing effect of ketamine at 12.5 mg/kg was suppressed by nimodipine (calcium blocker) (31,32), ceruletide (CCK-like deca peptide, which suppresses the central dopaminergic systems through a modification of afferent transmission) (33) or haloperidol (dopamine receptor antagonist) (24). These results also indicate that the stimulative effect of ketamine appears through the calcium-depend ent dopaminergic mechanism, like that of MK-801 (22).…”
Section: Discussionmentioning
confidence: 99%